The Criminogenic Dynamics of Methamphetamine Abuse: A Differential Association Theory Approach (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
Methamphetamine abuse remains a critical challenge in Indonesia because it threatens public health, social stability, economic development, and national security. This study aims to analyze the criminogenic dynamics underlying methamphetamine abuse and to explain how social interaction and peer environments facilitate the learning of drug-related behavior through Edwin H. Sutherland's Differential Association Theory. The study employed a non-empirical qualitative design using normative juridical and criminological approaches. Secondary data were collected through an extensive review of statutory regulations, scholarly literature, previous research, court decisions, and official publications of the National Narcotics Board (BNN). The data were analyzed using qualitative content analysis. The findings indicate that methamphetamine abuse results from the interaction between internal and external criminogenic factors. Internal factors include psychological vulnerability, weak self-control, identity exploration, and curiosity, whereas external factors comprise family disorganization, deviant peer associations, weakened social control, educational limitations, and economic hardship. Differential Association Theory further explains that methamphetamine abuse is acquired through sustained interaction within intimate social groups, where individuals learn criminal techniques, motives, rationalizations, and favorable definitions toward drug use. These findings suggest that effective prevention requires integrated strategies combining family strengthening, positive social environments, education, rehabilitation, and sustained law enforcement to disrupt criminogenic social learning processes.